2020
DOI: 10.1080/15384101.2020.1749468
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA RUSC1-AS1 promotes tumorigenesis in cervical cancer by acting as a competing endogenous RNA of microRNA-744 and consequently increasing Bcl-2 expression

Abstract: The expression of a long noncoding RNA termed RUSC1-AS1 is dysregulated in breast cancer and laryngeal squamous cell carcinoma, and this dysregulation affects various tumor-associated biological processes. To our knowledge, the expression status and detailed roles of RUSC1-AS1 in cervical cancer as well as its regulatory mechanisms of action remain unknown. Therefore, the objectives of this study were to measure RUSC1-AS1 expression in cervical cancer, investigate the effects of RUSC1-AS1 on cervical cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
1
22
0
1
Order By: Relevance
“…Interestingly, abnormal expression of DSCR8 is associated with poor prognosis in the liver (Wang et al, 2018) and ovarian cancer (You et al, 2020). Abnormal expression of RUSC1-AS1 has also been implicated in the development of cervical cancer (Guo et al, 2020). FGD5-AS1 has been shown to promote colorectal cancer cell proliferation, migration, and invasion by functioning as a sponge for miR-302e and regulating CDCA7 expression FIGURE 9 | GSEA and GSVA in high-and low-risk osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, abnormal expression of DSCR8 is associated with poor prognosis in the liver (Wang et al, 2018) and ovarian cancer (You et al, 2020). Abnormal expression of RUSC1-AS1 has also been implicated in the development of cervical cancer (Guo et al, 2020). FGD5-AS1 has been shown to promote colorectal cancer cell proliferation, migration, and invasion by functioning as a sponge for miR-302e and regulating CDCA7 expression FIGURE 9 | GSEA and GSVA in high-and low-risk osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported to serve as a prognostic indicator of hepatocellular carcinoma (HCC) [ 9 ] and promote HCC proliferation through regulating the NOTCH signaling pathway [ 39 ]. Besides, RUSC1-AS1 serves as a ceRNA in cervical cancer by binding with miR-744 and thus increases the expression of the anti-apoptotic protein BCL-2 [ 10 ]. In laryngeal squamous cell carcinoma, RUSC1-AS1 is also reported to be a ceRNA as well as a prognostic indicator [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA RUSC1-AS1 is reported to promote tumor growth in hepatocellular carcinoma [ 9 ], cervical cancer [ 10 ] and breast cancer [ 11 ]. Zhang et al reported that RUSC1-AS1 is associated with unfavorable prognosis in osteosarcoma [ 12 ], but its role has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…The extemporaneous examination of the hysterectomy specimen is not recommended, as the speci city is low on myometrial in ltration and the histological grade. [44]. Analysis of the operative specimen after para n embedding allows in 25% of cases a grade change between the biopsy and the operative specimen and in 5% of cases a histological change and speci es the FIGO stage, myometrial invasion, the macroscopic size of the tumor, the depth of the invasion, the lymph node invasion, the presence of vascular emboli, the extension to the uterine cervix and the ectopic extension.…”
Section: Anatomopathological Pro Lementioning
confidence: 99%